Supartz (Sodium Hyaluronate) for the Treatment of Knee Osteoarthritis: A Review of Efficacy and Safety - Bronstone, Amy (Clin Med Insights Arthritis Musculoskelet Disord, 2019)
As concerns about the safety of systemic oral pharmacologic treatments for knee osteoarthritis (OA) mount, clinicians have increased the use of intra-articular hyaluronic acid (IA-HA) in managing mild-to-moderate knee OA. Supartz (sodium hyaluronate; Seikagaku Corporation, Tokyo, Japan) is the first IA-HA product to be approved in the world and has the longest history of global use. In this review, we summarize evidence supporting Supartz efficacy and safety, including data from pivotal clinical trials that resulted in approval of Supartz in the United States and Japan, the safety of single and repeated courses of Supartz, and Supartz efficacy using objective outcomes and in special populations. There is strong evidence that single 5-week courses of Supartz provide clinically meaningful reductions in pain and improved function for up to 6 months without risk of serious side effects or complications. Repeated courses of Supartz are as safe as single courses and have an extremely low risk of infection. Findings from promising initial studies, which suggest that Supartz may improve muscle strength, gait pattern, and balance, should be confirmed in randomized controlled trials.